Children with a history of prematurity presenting with snoring and sleep-disordered breathing - Manuel, A.M.; Witmans, M.; El-Hakim, H. (Lippincott, Williams & Wilkins, 2013)
Objectives/Hypothesis To report on the prevalence of premature (PM) birth in a consecutive series of children treated for snoring and sleep-disordered breathing (S/SDB), the parameters specific to their management and variables predictive of disease severity.